Research progress of family-centered hospice care in patients with advanced cancer (以家庭为中心的临终关怀模式在癌症患者中的研究进展) - SONG Xia (宋霞); TAO Yuexian (陶月仙); LEI Yuling (雷玉铃); LIU Chengyi (刘程怡) (Association of Integrative Nursing, 2023)
Family support plays an important role in cancer patients. This article provides an overview of the origins, intervention content, and current status of implementation, and explores the research progress of the family-centered hospice care model as applied to the field of cancer, with the aim of providing reference for community-based end-of-life care. (家庭的支持在癌症患者中起着重要作用。本研究就开展以家庭为中心的临终关怀在癌症领域中应用的研究进展进行综述, 旨在为国内护理人员开展以家庭为中心的临终关怀提供参考。)